(untitled) (International Journal of Innovative Computing, 2026)
This study aims to optimize patient flow within the Green Zone of a Hospital Emergency Department in Kuala Lumpur by focusing on reducing patient waiting times and improving staff workload caused by overcrowding and operational inefficiencies. A model was developed to replicate current Green Zone operations and evaluate scenarios to optimize staff allocation and identify the bottlenecks by using Discrete Event Simulation (DES) in ARENA software. The model has been verified by medical professionals and validated against real-world data with an acceptable deviation of less than 10%. Implementation of the optimized model significantly reduced average patient waiting times from 174.50 minutes to 60.65 minutes. Doctor utilization rates also decreased from 97.00% to 76.66%, indicating improved resource efficiency and workload distribution. The application of DES in optimizing patient flow within the Green Zone demonstrated significant improvements in both patient experience and operational efficiency. The approach holds potential for broader implementation across other departments and healthcare facilities in Malaysia.